Edge detection using neural network arbitration - Ramalho, Mário António da Silva Neves (1996)
A human observer is able to recognise and describe most parts of an object by its contour, if this is properly traced and reflects the shape of the object itself. With a machine vision system this recognition task has been approached using a similar technique. This prompted the development of many diverse edge detection algorithms.